Attack Level Of Coffee Fruit Borer Pest (Hypothenemus hampei) And Branch Borer Pest (Xylosandrus compactus) In Central Dempo District Pagaralam City - Arsi Arsi; Suparman SHK; Bambang Gunawan; Abu Umayah; Yulia Pujiastuti; Harman Hamidson; Chandra Irsan; Suwandi; Nurhasnah (Universitas PGRI Palembang, 2023)
Pagaralam is a city in South Sumatra Province with five districts: North Dempo, Central Dempo, South Dempo, North Pagaralam and South Pagaralam. The main commodity is coffee. Coffee cultivation has a major problem, namely the attack of fruit and branch borer pests because it can reduce the quality and productivity of coffee. This study was to determine the level of attack by fruit borer and branch borer in the Dempo Tengah sub-district. Coffee farmers in Pagaralam use monoculture and polyculture cultivation systems. This field practice method is observation, observation in this study, and interviews with coffee farmers. The results showed that the attack of young coffee berry borer pests can cause the fruit to wither and fall off, while ripe fruit has holes in its seeds. Branch borer attacks cause branches to wither and dry. The highest percentage of fruit and branch borer attacks on coffee plants was found in young mixed-aged coffee plantations. In conclusion, fruit borer and coffee branch borer are more susceptible to attacking coffee at a young age, because young coffee plants have soft plant organs. Lush shade creates high humidity and low temperatures, which can make it easier for pests to breed.